Social media, participation, peer pressure, and the European refugee crisis: a force awakens? - Gustafsson, Nils (AoIR Selected Papers of Internet Research, 2016)
This paper studies the way young people in Sweden used social media to discuss and mobilise during the European refugee crisis, with a special focus on peer pressure and social interaction. In September 2015, an explosion of voluntary activities occurred, many of which were grouped under the personal action frame (Bennett & Segerberg, 2013) of _Refugees Welcome_. Civil society organisations and temporary networks set up shop in train stations and in ports, helping refugees and sometimes interfering with official efforts and policy. The outburst of voluntarism was coupled with a popular opinion strongly in favour of continuing Sweden’s refugee-friendly policy, also in the face of record numbers. This all changed in a number of months, however, with shifts in policy, public mood, and voluntarism. These events calls for revisiting a number of recent theoretical developments in participation research: Bennett & Segerberg’s (2013) notions of _personal action frames_ and _connective action_, as well as Amnå and Ekman’s (2013) _latent participation_, describing emerging personalised ways of interacting with social and political issues of the day, and occasionally becoming - sometimes very temporarily - mobilised into action. In this exploratory study, focus group interviews with Swedish 16-25 year olds are used to allow young people in a formative stage of life and who are not necessarily active or organised in politics or social issues to discuss their attitudes and experiences in relation to the refugee crisis with their peers. The purpose is to evaluate and develop concepts of mobilisation and connective action.